PENGARUH LATIHAN PLIOMETRIK MODIFlKASI TERHADAP POWER OTOT TUNGKAI PADA OLAHRAGA Abstract BOLAVOLI - Fauzi Fauzi (Jurnal Cakrawala Pendidikan, 2007)
Plyometrics is about a form of burst-of-power trammg withcharacteristic usageof very strong and quick muscle contractionsand also represents isometric, eccentric, and isotonic trainingcombinations. The trainingof plyometrics is with knee-tuck jumpmodification andof side-front-back jump combination models. Aresearch this article is about is aimed at proving that both practicemodels above can improve leg power and that plyometric practice isable to have great influences on leg power improvement.The populationof the research study consists of male-athletestudentsof the volleyball school of the Sport Science Faculty, StateUniversityof Yogyakarta. The sample used consisted of 48students/athletes selected with an intake technique by meansofpurposive sampling. The trainees were divided into similar threegroups: the first group was treated with the knee-tuck jumpmodification, the second group was treated with side-front-backjump combination, and the third group was givenno specifictreatmentto function as a control group. Before and after thetreatments, a vertical jump test was administered. A normality teston the data showed that the data distribution was normal and ahomogeneity test on the three groups showed that they werehomogeneous. From an Anova test on two treatments with a controlgroup, significant differences were found.The resultsof data analysis indicate that plyometric knee-tuckjump modification and side-front-backjump combination training bymeansof the program for the research study is proven to haveinfluences on the increaseof leg muscle power of students/athlete of the volleyball school. The side-front-back jump combinationmodel is more influential than the knee-tuck jump modificationmodel.